PEMANAFAATAN INFORMASI AKUNTANSI DAN ARUS KAS DALAM PENETAPAN RETUR SAHAM PADA PERUSAHAAN FOOD AND BEVERAGES DI BURSA EFEK INDONESIA PERIODE TAHUN 2012-2016 - Nurdiana, Diah (REKAMAN (Jurnal Riset Ekonomi Bidang Akuntansi dan Manajemen), 2018)
This study aims to obtain empirical evidence regarding the use of accounting information and cash flow on stock returns in food and beverage companies listed on the Indonesia Stock Exchange either partially or simultaneously.The research method used was descriptive using secondary data. The variables studied were Accounting Information, operating cash flow, investment cash flow, funding cash flow and stock returns. The population used in this study were 12 food and beverage companies listed on the Indonesia Stock Exchange (IDX) which reported complete financial reports. The data collection technique in this study was carried out by means of a document review, namely tracking the financial statements of food and beverage companies in 2012-2016. on the BEI official website (www.idx.com). The results of the research conducted, the multiple linear regression equation is obtained as follows: Å¶ = 0.089 - 0.386 X1 - 0.034X2 - 0.008 X3 + 0.013 X4. The classic assumption test results can be concluded that the normality test is normally distributed, there is no multicollinearity, there is no heteroscedasticity and there is no positive or negative autocracy, the BLUE (Best Linear Unbiased Estimator) regression model has been fulfilled. Hypothesis testing partially shows that the total assets independent variable which affects stock returns, while other independent variables show no effect on stock returns. From the results of calculations through eviews 8 it can be seen that the probability value F is 7.123. Thus, the variables namely net income, operating cash flow, investment cash flow, funding cash flow, and total assets together have a significant effect on stock returns. The results of the analysis of the determination coefficient show the amount of R2 of 0.543. This means that the effect of the variable net income, operating cash flow, investment cash flow, funding cash flow, and total assets on stock returns is 54.3%, while the rest (100% - 54.3% = 45.5%) can be explained by other independent variables such as cash dividends. The results of the analysis obtained the R number of 0.737 then compared with the interpretation table of the correlation coefficient the value of 0.737 is in the range of 0.60 - 0.800 this indicates that the relationship between the independent variables on the dependent variable is strong